Two copper(i) cyanide coordination polymers modified by semi-rigid bis(benzimidazole) ligands: syntheses, crystal structures, and electrochemical and photocatalytic properties. Issue 43 (14th October 2016) - Cui, Jing-Wang; An, Wei-Jia; Van Hecke, Kristof; Cui, Guang-Hua
Abstract : Two Cu(i ) cyanide complexes with semi-rigid bis(benzimidazole) ligands were synthesized and characterized. Both complexes manifest photocatalytic activities for the degradation of methylene blue. Abstract : Two Cu(i ) cyanide coordination polymers (CPs), namely, [Cu2 (L1)(CN)2 ] n (1 ) and [Cu2 (L2)(CN)2 ] n (2 ) (L1 = 4, 4′-bis(2-methylbenzimidazol-1-ylmethyl)biphenyl, L2 = 4, 4′-bis(5, 6-dimethylbenzimidazol-1-ylmethyl)biphenyl) were synthesized and structurally characterized by single crystal X-ray diffraction, IR spectroscopy, X-ray powder diffraction and elemental analysis. The cyanide ligands in these CPs are generated in situ from the C–C bond cleavage of acetonitrile under solvothermal conditions, which is environmentally friendly and used conveniently. CP1 features a three-fold interpenetration 3D framework consisting of Cu10 (CN)6 (L1)4 rings, which represents the first investigation on introducing bis(benzimidazole) ligands into copper(i ) cyanide CPs withThSi 2 topology, while CP2 exhibits a two-dimensional (6, 3) layered structure containing Cu6 (CN)4 (L2)2 rings. The thermal stabilities, and photoluminescence and electrochemical behavior in the solid state of CPs1 and2 have been investigated in detail. Moreover, both CP1 and CP2 manifest promising photocatalytic activities (photodegradation efficiency using CP1 is 90.8% and using CP2 is 87.2%) for the degradation of methylene blue (MB) under UV light irradiation. A possible photocatalytic mechanism is suggested by introducing t -butyl alcohol (TBA) as a widely used ˙OH scavenger.